2008
DOI: 10.1007/s00439-008-0569-6
|View full text |Cite
|
Sign up to set email alerts
|

The MSX1 allele 4 homozygous child exposed to smoking at periconception is most sensitive in developing nonsyndromic orofacial clefts

Abstract: Nonsyndromic orofacial clefts (OFC) are common birth defects caused by certain genes interacting with environmental factors. Mutations and association studies indicate that the homeobox gene MSX1 plays a role in human clefting. In a Dutch case-control triad study (mother, father, and child), we investigated interactions between MSX1 and the parents' periconceptional lifestyle in relation to the risk of OFC in their oVspring. We studied 181 case-and 132 control mothers, 155 case-and 121 control fathers, and 176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…In this regard, it is interesting to note effects of maternal genotype and maternalspecific environmental modifiers such as smoking, drinking and vitamin intake during pregnancy on oral cleft susceptibility have been previously reported in various studies. 2,[10][11][12][13][14][15][16][17][18][19] However, it should be noted that the parental asymmetry tests we applied here do not specifically test for maternal effects which would be expected to occur via alterations of the in utero environment. Calculation of genomic inflation factors for the MAT and PAT tests showed a small increase for the MAT compared with the PAT in all categories, this increased inflation factor in the MAT does not discern the underlying cause, being consistent with either a true excess of biological associations with the maternally inherited alleles, or alternatively differing population structure between the two parental populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is interesting to note effects of maternal genotype and maternalspecific environmental modifiers such as smoking, drinking and vitamin intake during pregnancy on oral cleft susceptibility have been previously reported in various studies. 2,[10][11][12][13][14][15][16][17][18][19] However, it should be noted that the parental asymmetry tests we applied here do not specifically test for maternal effects which would be expected to occur via alterations of the in utero environment. Calculation of genomic inflation factors for the MAT and PAT tests showed a small increase for the MAT compared with the PAT in all categories, this increased inflation factor in the MAT does not discern the underlying cause, being consistent with either a true excess of biological associations with the maternally inherited alleles, or alternatively differing population structure between the two parental populations.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, environmental studies have indicated maternal smoking, and potentially alcohol consumption, during pregnancy greatly increase the risk of clefting in offspring, with some evidence of genetic interactions. 2,10,11 Similarly, according to several studies, multi-vitamin supplements with or without folic acid taken during pregnancy have been shown to decrease the risk of oral clefting, with a stronger effect seen in CL/P as compared with CPO. [12][13][14] If levels of circulating folate are influenced by genetic factors, then it can be hypothesized any maternal genes involved in dictating circulating folate levels could also alter the risk of OFCs in the fetus.…”
Section: Introductionmentioning
confidence: 98%
“…[25][26][27] It was shown that smoking by both parents interacts with a specific allelic variant of MSX1, which significantly increase the OFC risk for their offspring. 28 Moreover, a novel approach was developed by Wehby et al 26 to study the role of maternal smoking and OFC, in which they found out that smoking before and during pregnancy increased the risk of OFC by about 4-5 times at the sample average smoking rate. Furthermore, in a recent genome-wide analysis study (GWAS), biases for maternally inherited genetic factors influencing the risk of OFC was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] However, MSX1 also clearly affects the common human oral cleft phenotypes, as demonstrated through multiple genetic studies. [15][16][17][18][19][20] Yet, in all but a single case report, 5 MSX1 apparently functions as a complex disease determinant for oral clefting. In this context, there have been multiple reports of MSX1 missense mutations within sporadic clefting cases, 17,18,21,22 but all these reports suffer from a lack of power to discern disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental perturbations, such as maternal smoking, can also influence craniofacial phenotypes, for example, maternal smoking in the presence of the CA4 homozygous state increased the risk of clefting. 19,46 Thus, in the interest of future meta-analysis of these questions, we report these data below.…”
Section: Introductionmentioning
confidence: 99%